Examining Passengers’ Satisfaction with Public Transportation in The Rise of Health Concerns - Arie Indra Gunawan; Arizzal Primayandi; Dlukha Nurkholik (Journal of Marketing Innovation (JMI), 2022)
As the most frequently used mode of public transportation, train service providers must ensure the safety of passengers since the rise in health concerns. PT KAI has implemented health regulations in line with government recommendations. However, it is necessary to understand, measure, and accommodate passengers' perceptions of service quality as a way of enhancing safety. This study employs a quantitative approach by collecting online questionnaires from 404 passengers who use long-distance train services in Bandung Station. The data analysis is carried out using SPSS and SEM-PLS methods. The result shows that passengers perceived the safety, service quality, satisfaction, and reuse intention positively. Then, perceived safety and perceived service quality influenced passengers’ satisfaction. In addition, the satisfaction increased willingness to reuse intentions for long-distance train services. Thus, companies must be able to build a positive experience for their passengers and convince them that it is safe and suitable to use public transportation.